Mewujudkan Kesadaran Mahasiswa akan Lingkungan melalui Kegiatan Bersih-bersih Taman - Elly Christanty Gautama; Andini Ika Arianti; Rahayu Mardikaningsih; Mila Hariani; Nelud Darajaatul Aliyah (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The campus park cleanup is a concrete effort to raise student awareness of the importance of cleanliness and the preservation of green open spaces. This program focuses not only on physical activities such as cleaning, land management, and planting, but also aims to foster pro-environmental behavior through direct student involvement. Using the Participatory Action Research (PAR) method, this activity involves students in every stage, from planning, implementation, and evaluation, thus encouraging dialogue, cooperation, and a sense of shared responsibility. The implementation results show high student enthusiasm and participation, as evidenced by their dedication in cleaning the park area, removing weeds, cultivating the soil, and planting ornamental and edible plants. This activity concluded that environmental awareness was formed, solidarity was strengthened, and a sense of ownership of the campus environment grew. In addition to impacting the physical condition of the park, this activity also serves as an educational medium to instill environmental values ​​from an early age. It is hoped that such activities can be carried out sustainably to create a clean and comfortable campus environment for the entire academic community.